Influence of the Cultivator Working Body Parameters on the Soil Crumbling Quality - S. I. Kambulov; G. G. Parkhomenko; O. S. Babenko; I. V. Bozhko (Сельскохозяйственные машины и технологии, 2022)
It was shown that soil is a specific type of natural resource that can be renewed when reasonably cultivated by various tillage methods. It requires the availability of working bodies that meet the qualitative agrotechnical indicators of the technological process. (Research purpose) To improve the design of the working body meeting the qualitative agrotechnical indicators of the shallow tillage technological process. (Materials and methods) The main agrotechnical indicators of the cultivator's working body were determined. (Results and discussion) It was proved that the working bodies developed at the Agrarian Scientific Center "Donskoy" meet the agrotechnical requirements for the indicators of the shallow tillage technological process in terms of the crumbling quality: the content of fractions less than 25 millimeters in size in the treated soil layer is 81-92 percent in terms of quantitative composition. It was found out that the highest quality of seam crumbling during the shallow tillage process with a predominant content of fractions less than 25 millimeters in size (on average 90-91 percent) was made possible with the help of a working body with a 30-degree rack sharpening angle. It was determined that at the same time the share of erosive dust-like particles increased by 1.3-3.0 percent, which is unacceptable due to the agrotechnical requirements for shallow tillage. (Conclusions) Working bodies with a rack sharpening angle of 50 and 70 degrees and a paw opening angle of 94, 104 and 114 degrees compile with agrotechnical requirements for all qualitative indicators of the shallow tillage technological process and can be applied as anti-erosion ones when used in the combined units equipped with a device for mulching the surface soil layer on stubble backgrounds without preliminary processing.